Successive bilateral thoracotomy in the treatment of bilateral pulmonary hydratic cyst - Delgado, Bolívar; Macedo, Juan C; Díaz, Barret (Cirugía del Uruguay, 2021)
Ten cases of bilateral pulmonary hydatidosis were treated through successive bilateral thoracotomy in the Thoracic Surgery Service of the Saint-Bois Hospital. Case material is analyzed with special reference to the general conditions of patients, topography and number of cysts, approach and operatory techniques employed. This procedure. was highly successful in ali operated patients. It is important that such surgery only be performed where anesthesists, X-Ray controls and Recuperation Services with personnel traine.d in this type of surgery, be available.